Antecedents of Store Loyalty - Exploring the Role of Store Affect - Rabbanee, Fazlul; Ramaseshan, Balasubramani; Vinden, Amy (ANZAM, 2012)
This paper investigated the role of store affect on store loyalty, a topic that has not been explored adequately. It examined the mediating role of store affect in relationships between store loyalty and its antecedents namely perceived value and store trust. The data were collected from 470 shoppers from a large shopping mall in Australia through a structured questionnaire. The paper revealed that perceived value, store trust and store affect have significant direct and/or indirect impact on store loyalty. The findings of the study also revealed that that store affect partially mediates the relationship between perceived value and store loyalty; and fully mediates the relationship between store trust and store loyalty. Managerial implications of the findings are discussed.